1978
DOI: 10.1084/jem.148.4.1068
|View full text |Cite
|
Sign up to set email alerts
|

Virus-induced diabetes mellitus. XV. Beta cell damage and insulin-dependent hyperglycemia in mice infected with coxsackie virus B4.

Abstract: Coxsackie virus B4 that had been passaged in cultures enriched for pancreatic beta cells produced a diabetes-like syndrome when inoculated into SJL/J mice. The infection resulted in insulitis and destruction of beta cells. Viral antigens were found in beta cells by staining with fluorescein-labeled antibody to Coxsackie virus B4. The destruction of beta cells led to a decrease in the immunoreactive insulin content of the pancreas and hypoinsulinemia. The reduction in immunoreactive insulin correlated inversely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
99
0
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(100 citation statements)
references
References 26 publications
0
99
0
1
Order By: Relevance
“…Our previous results have shown that primary human beta cells are susceptible to infections by prototype strains of several coxsackie viruses (CV) and that the infection could result in either impaired beta-cell function or beta-cell death (CBV-3, CBV-4 and CBV-5) or both, or has no apparent immediate adverse effects, as shown for CAV-9 [22]. Susceptibility of primary human beta cells to CBV-3, 4 and 5 have also been shown in some other studies [21,23,24,25]. In our study, we assessed diabetogenic properties of different enteroviruses including several serotypes of echoviruses.…”
mentioning
confidence: 86%
“…Our previous results have shown that primary human beta cells are susceptible to infections by prototype strains of several coxsackie viruses (CV) and that the infection could result in either impaired beta-cell function or beta-cell death (CBV-3, CBV-4 and CBV-5) or both, or has no apparent immediate adverse effects, as shown for CAV-9 [22]. Susceptibility of primary human beta cells to CBV-3, 4 and 5 have also been shown in some other studies [21,23,24,25]. In our study, we assessed diabetogenic properties of different enteroviruses including several serotypes of echoviruses.…”
mentioning
confidence: 86%
“…Thus, the in vitro susceptibility of B cells may not be a true reflection of their in vivo susceptibility. Nonetheless, when Coxsackie viruses B3 and B4 and reovirus type 3 were passaged multiple times in murine pancreatic B cell cultures, these viruses infected and destroyed B cells to produce a diabetes-like syndrome in susceptible mice [10,25,26]. These studies suggest that under appropriate circumstances, a number of viruses can infect and destroy insulin-producing B cells.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, infection is associated with either an increased risk (as with CVB1 infection) or a decreased risk (as with CVB3 and CVB6 infection) [82,83]. CVB infects isolated human and murine beta cells [84][85][86]. In human islets, beta cell infection is associated with IFNα production [17].…”
Section: How Might Bystander Lymphocyte Activation Contribute To Diabmentioning
confidence: 99%